Herpes Zoster - Cut Desy Diana Sari; Wizar Putri Mellaratna (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Herpes zoster (HZ) or shingles is clinically manifested by the reactivation of endogenous latent infection of the varicella zoster virus (VZV) in the dorsal roots of sensory fibers and cranial or autonomic nerve ganglia. This reactivation occurs after the primary infection when decrease of immune system. A case of a 78-year-old patient came with eritematous fluid-filled vesicle, burning pain on the left side of her face. This patient was given non-medical therapy such as education on maintaining hygiene, do not scratching the lesions and 0.9% Nacl compresses on the vesicle area. Medical therapy was given topical and systemic therapy.